CD73 mitigates ZEB1 expression in papillary thyroid carcinoma - Vedovatto, Samlai (2024)
Background: ZEB1, a core transcription factor involved in epithelial-mesenchymal transition (EMT), is associated with aggressive cancer cell behavior, treatment resistance, and poor prognosis across various tumor types. Similarly, the expression and activity of CD73, an ectonucleotidase implicated in adenosine generation, is an important marker of tumor malignancy. Growing evidence suggests that EMT and the adenosinergic pathway are intricately linked and play a pivotal role in cancer development. Therefore, this study focuses on exploring the correlations between CD73 and ZEB1, considering their impact on tumor progression. Methods: We employed CRISPR/Cas9 technology to silence CD73 expression in cell lines derived from papillary thyroid carcinoma. These same cells underwent lentiviral transduction of a reporter of ZEB1 non-coding RNA regulation. We conducted studies on cell migration using scratch assays and analyses of cellular speed and polarity. Additionally, we examined ZEB1 reporter expression through fow cytometry and immunocytochemistry, complemented by Western blot analysis for protein quantifcation. For further insights, we applied gene signatures representing diferent EMT states in an RNA-seq expression analysis of papillary thyroid carcinoma samples from The Cancer Genome Atlas. Results: Silencing CD73 expression led to a reduction in ZEB1 non-coding RNA regulation reporter expression in a papillary thyroid carcinoma-derived cell line. Additionally, it also mitigated ZEB1 protein expression. Moreover, the expression of CD73 and ZEB1 was correlated with alterations in cell morphology characteristics crucial for cell migration, promoting an increase in cell polarity index and cell migration speed. RNA-seq analysis revealed higher expression of NT5E (CD73) in samples with BRAF mutations, accompanied by a prevalence of partial-EMT/hybrid state signature expression. Conclusions: Collectively, our fndings suggest an association between CD73 expression and/or activity and the posttranscriptional regulation of ZEB1 by non-coding RNA, indicating a reduction in its absence. Further investigations are warranted to elucidate the relationship between CD73 and ZEB1, with the potential for targeting them as therapeutic alternatives for cancer treatment in the near future.